Potentiality of Seven Cultivars of Pennisetum Typhoides (Burm. F. Stapf.) Hubbard to Withstand Soil Salinity - Jhamb, R B; Bhandari, D C; Sen, D N (Annals of Arid Zone, 2016)
Soil salinity of the level of 11.3 mmhos/cm (in terms of electrical conductance) adversely affected the seed germination, fresh and dry matter produced per unit by 3 days old seedlings of all the cultivars of Pennisetum typhoides, unlike the dry matter production on fresh weight basis, which increased considerably over other soil salinity levels having EC lesser than 11.3 mmhos/cm. On the basis of seed germination potential and dry mailer production, cultivar BJ 104 was found to be the most salt tolerant.